IMPLEMENTATION OF INTERNATIONAL ENTREPRENEURIAL ACTIVITY IN THE CONTRACT OF EUROPEAN INTEGRATION - SHUBA, TETYANA; MIKISHA, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the peculiarities of the implementation of international business activities in the context of European integration. The main ways to improve and simplify the conditions for enterprises to enter the foreign market are identified. Opportunity to learn from EU countries and set new standards, as the international market requires a high level of enterprise development and high quality services and goods. The issues concerning the formation of strategies for the development of enterprises and the urgent solution of current problems that may hinder the implementation of successful international business activities are considered. European integration is an opportunity to realize the entrepreneurial potential of the country and ensure its economic development. Therefore, the main task for modern entrepreneurs is to enter the international market, because it ensures the dynamic development of their business in the context of the spread of integration processes. Intensification of European integration processes allows to find effective ways of stimulation on the basis of studying the experience of European countries. The purpose of these processes is to establish close cooperation between the EU and Ukraine in the economic sphere. This cooperation does not provide any guarantees for the economic development of the country, but opens up opportunities for this to be realized. EU integration tools can increase the efficiency and competitiveness of enterprises, and the existing structural funds support these processes. European integration is only a complement to the implementation of international business, it can not replace domestic efforts and entrepreneurial activity in the country. Currently, the main task for Ukraine is to formalize agreements with the EU on the implementation of the principles set out in the AMB. European integration is the main goal of Ukraine - it can be an opportunity to build an economically developed state, strengthen and find new ties in the world system of international relations. European integration is a profitable way for those companies that want to realize themselves in the international market and is one of the main ways to develop and improve business.
Keywords: European integration; international entrepreneurship; European Union; business; state regulation